2023
DOI: 10.1002/admi.202300162
|View full text |Cite
|
Sign up to set email alerts
|

Combining Rigid Cellulose Nanocrystals and Soft Silk Proteins: Revealing Interactions and Alignment in Shear

Ilona Leppänen,
Suvi Arola,
Alistair W. T. King
et al.

Abstract: Natural materials, such as silk and cellulose, have an inspiring set of properties, which have evolved over hundreds of millions of years. In this study, cellulose nanocrystals (CNCs) and regenerated silk fibroin (RSF) are combined to evaluate their suitability for filament formation. This is assessed by tuning and characterizing the interactions between these two materials and finally by studying the alignment of the mixtures under shear. To modify the interactions between CNCs and silk, CNCs with varying sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…For instance, Leppänen et al observed an increase in the binding between CNC and silk fibroin by amine–amine linked between succinimidyl-6-hydrazinonicotinate acetone hydrazone (SANH) and succinimidyl-4-formyl benzoate (SFB) moieties, but it induced a not-wanted nanocluster formation. 109 Other molecules, such as the combination of tetraethylene pentamine (TEPA) and GMA, form longer linkers capable of connecting cellulose to the rhodamine chromophore (RC). In this configuration, cellulose suffers modification through the cyclohexane ring in the presence of cerium ammonium nitrate, and aldehyde functional molecules such as RC attaches to cellulose – GMA – TEPA by imine reaction in DMF medium.…”
Section: Multi-building Linkers In Bioconjugated Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Leppänen et al observed an increase in the binding between CNC and silk fibroin by amine–amine linked between succinimidyl-6-hydrazinonicotinate acetone hydrazone (SANH) and succinimidyl-4-formyl benzoate (SFB) moieties, but it induced a not-wanted nanocluster formation. 109 Other molecules, such as the combination of tetraethylene pentamine (TEPA) and GMA, form longer linkers capable of connecting cellulose to the rhodamine chromophore (RC). In this configuration, cellulose suffers modification through the cyclohexane ring in the presence of cerium ammonium nitrate, and aldehyde functional molecules such as RC attaches to cellulose – GMA – TEPA by imine reaction in DMF medium.…”
Section: Multi-building Linkers In Bioconjugated Systemsmentioning
confidence: 99%
“…For instance, MCC and rhodamine chromophore exhibit excellent optical signals and selectivity (detection limit on Hg 2+ < 9.18 × 10 −7 M) upon contact with mercury, playing a notable role in detecting and removing the metal in tap water. 109 Alternatively, CNC coupled with the pH-indicator dye (5 and 6)-carboxy-2′,7′-dichloro-fluorescein, and l -leucine amino acid were used to construct fluorescent nanoparticles for pH-sensing, demonstrating fluorescent properties when the pH of the media was increased (Fig. 6(b)).…”
Section: Lignocellulosic Bioconjugated Applications and Propertiesmentioning
confidence: 99%
“…One of the first AFM-IR demonstrations was reported in 2005 by Dazzi et al [4], who presented AFM-IR spectra of single bacterial cells. Further on, this technique became more refined and found its way into many and highly diverse fields of application, including virology, DNA nanotechnology, polymer science, and materials science [5][6][7][8][9]. The importance of AFM-IR steadily grew over the past decade and its development has been described in detail in several review papers [1,3,9,10].…”
Section: Introductionmentioning
confidence: 99%